2022
DOI: 10.1007/jhep04(2022)072
|View full text |Cite
|
Sign up to set email alerts
|

String stars in anti de Sitter space

Abstract: We study the ‘string star’ saddle, also known as the Horowitz-Polchinski solution, in the middle of d + 1 dimensional thermal AdS space. We show that there’s a regime of temperatures in which the saddle is very similar to the flat space solution found by Horowitz and Polchinski. This saddle is hypothetically connected at lower temperatures to the small AdS black hole saddle. We also study, numerically and analytically, how the solutions are changed due to the AdS geometry for higher temperatures. Specifically,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…scattering amplitudes and generalize the single-valued multiple zeta values that occur in the spectral problem [13,15,40]. Finally, we also provide numerical values for the first three corrections to the leading strong-coupling behavior, finding perfect agreement with the analytic calculation [41,42] of the first correction. 1 The second aim of this paper is to extend said results for the Hagedorn temperature to a class of integrable deformations of the maximally supersymmetric Yang-Mills theory and to include chemical potentials.…”
Section: Jhep07(2022)136 1 Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…scattering amplitudes and generalize the single-valued multiple zeta values that occur in the spectral problem [13,15,40]. Finally, we also provide numerical values for the first three corrections to the leading strong-coupling behavior, finding perfect agreement with the analytic calculation [41,42] of the first correction. 1 The second aim of this paper is to extend said results for the Hagedorn temperature to a class of integrable deformations of the maximally supersymmetric Yang-Mills theory and to include chemical potentials.…”
Section: Jhep07(2022)136 1 Introductionsupporting
confidence: 53%
“…Moreover, since the first appearance of the present paper on the arXiv, the coefficients c 0 and c 1 have been analytically calculated by considering the inverse Hagedorn temperature as the radius for which a winding mode becomes massless [41,42]:…”
Section: Jhep07(2022)136mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the author conjectured the existence of complex HP-like solutions with higher winding and momentum numbers which would explain the expected ramp-up in time of this variant in weakly-coupled string theories. An HP-like solution with an asymptotically AdS factor of the geometry was found in [28], its instability and a potential transition to a small black hole in AdS were also discussed. The authors of [29] found a family of HP-like solutions that asymptote to S 1 β × R 6 where β corresponds to the inverse Hagedorn temperature, and also identified worldsheet conformal field theories (CFTs) that describe them.…”
Section: Jhep10(2022)112mentioning
confidence: 98%